La–doped ZnO–rGO nanocomposites: Synthesis and characterization as photocatalyst for effective degradation of bromothymol blue dye in water - Moro Haruna; John Kwakye; Eric Selorm Agorku; Francis Opoku; Noah Kyame Asare-Donkor; Anthony Apeke Adimado (Results in Materials, 2023)
Several techniques for eliminating organic dyes and pesticides present in water and wastewater have been developed to lessen their negative environmental effects. The use of semiconductor photocatalysts to break down organic pollutants like dyes and insecticides has garnered a lot of interest recently. In this work, we have prepared simple, quick, and high–yielding La–doped ZnO–rGO nanoparticles that can be used for photocatalytic degradation. The prepared nanoparticles were characterized by various methods including morphological, optical, and photocatalytic properties using cutting–edge technologies like Transmission electron microscopy, energy dispersive spectroscopy, ultraviolet–visible spectroscopy, X–ray diffraction and scanning electron microscopy. The study investigated the photocatalytic action of La–doped ZnO–rGO nanocomposites under visible light irradiation and bromothymol blue as a module dye. According to the findings, La–doped ZnO–rGO nanoparticles demonstrated discernible photocatalytic performance, with the 0.6% La–doped ZnO–rGO exhibiting the best degradation percentage of 81% in 210 min and a rate constant of 1.158 × 10−3 min−1.